Kebaharuan Penelitian Global Mengenaai Kemampuan Pemahaman Konsep Matematis: Analisis Bilbliometrika dan Pemetaan Informasi - Ahmad Rizal Saqibul Fiqri; Suparman Suparman (Jurnal Karya Pendidikan Matematika, 2024)
he fundamental principle that can inspire students to demonstrate other mathematical abilities is their comprehension of mathematical concepts. The goal of the study is to describe some pertinent themes with fresh research potential and to examine journal articles that center on the theme of conceptual comprehension capacity. The scholarly literature on the subject of conceptual understanding capacity published between 2020 and 2023 is used in the bibliometric analysis developed for this study. Bibliometric techniques were created to use VOSviewer to examine scientific journals. The study's findings show that, throughout the previous 10 years, researchers' interest in the topic of conceptual understanding capacity applied in scientific publications has grown significantly. This study made adjustments and used 100 scientific papers that were found through a Dimensions database search. The findings of this study demonstrate that understanding mathematical concepts has emerged as a trend in junior high school research, with an emphasis on media and applications, as well as problem-based learning (PBL) models, beginning in the eighth grade.